“They have gone back to their country”: French landscapes and Inuit encounters in 18th century southern Labrador - Crompton, Amanda (Études/Inuit/Studies, 2015)
Although French and Basque fishing and whaling crews had been coming to southern Labrador since the early sixteenth century, colonization in a more permanent form would not begin until the late 17th and early 18th centuries. Emerging as an outgrowth of similar colonial efforts along Quebec’s Lower North Shore, colonization of Labrador was driven by Canadian interests and administered by colonial officials in Québec. However, the simple possession of Labrador landscapes was not equivalent to their successful exploitation. Detailed study of one land grant in Red Bay-St. Modet demonstrates how tenuous the possession of lands in Labrador could be, whether challenges came from French rivals or from Inuit raids. This article uses historical, cartographic, and archaeological evidence to discuss how the French established, contested, and used Labrador land concessions, and explores how Inuit reacted to the increasing encroachments of the French.